A Rare Case of Extramedullary Plasmacytosis. (August 2021) - Farraj, Kristen L.; Kaliounji, Aboud; Kagolanu, Deepthi; Khan, Nausheer
Plasmacytosis is the abnormal proliferation of plasma cells in tissue, bone, blood, or exudates. Mucous membrane plasmacytosis is a rare form of plasmacytosis that is usually idiopathic in nature. A 68-year-old female underwent a diagnostic and therapeutic esophagogastroduodenoscopy, which revealed a friable antral erythematous gastric fold and a gastric polyp. Subsequent pathological testing was positive for diffuse polyclonal plasma cell proliferation, which was suggestive of a gastric plasmacytosis. In this article, we report a rare presentation of mucous membrane plasmacytosis.